Editorial - Varghese, Bindi (Atna Journal of Tourism Studies, 2016)
This issue of Atna deliberates on the evolving facets of travel and leisure business. This volume makes a valuable contribution to the collection and presentation on the different aspects of tourism which will stimulate discussions on the travel and tourism arena among the business schools and professional advisors.This issue is focused towards enhancing better theoretical and conceptual clarity in the most recent emerging areas which are researched and explored by the academicians and the representatives of the trade.